PROBLEMATIKA PELAFALAN MANTRA PŪJĀ TRI SANDHYĀ (PERSPEKTIF PENDIDIKAN) - Ida Kade Suparta (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
The coaching of the Pūjā Tri Sandhyā mantra is still an emphasis in the learning process in non-formal boarding schools until now, but problems in reciting this mantra are still often found in students. The problems that arise are not only related to the differences in the mantras of the 1991 PHDI standard version and the previous version, but more serious problems related to the emergence of new word pronunciations. This phenomenon is very important to study in order to obtain a clear picture of the causes of this problem so that it can become a reference for interested parties in formulating appropriate solutions. This study uses a qualitative approach that implements observation, interviews, and documentation to collect representative data. The results of the study show that the factors causing the problems of reciting the Pūjā Tri Sandhyā mantra which have not been fully resolved to date are the lack of Sanskrit language development and the tendency of students to imitate this mantra without any correction. The orientation of the learning pattern at the pasraman does not emphasize how to chant mantras in accordance with Sanskrit provisions but tends to increase śraddhā and devotional service in the form of prayer habits.